Fremmede blikke: Ekkoer fra 1700-tallet hos Georg Brandes - Bjerring-Hansen, Jens (Danske Studier, 2024)
In the famous introduction to his series of lectures on Main Currents of Nineteenth Century Literature (published 1872–90) Georg Brandes (1842–1927) announced the necessity of an epochal transformation of the cultural and literary backwater of Denmark and the Nordic region as well as of a modern scientific approach to literary phenomena. Rhetorically and philosophically, this call for modernization was, however, also informed by texts and arguments from the Enlightenment of the eighteenth century, notably Voltaire’s Micromégas (1752). Brandes’ lifelong appropriation of the sci-fi novella sheds light on the legacy of the Enlightenment on his authorship, more specifically concerning his comparatist agenda as a literary critic and his cosmopolitan outlook as a politically engaged intellectual.